Karakteristik kemampuan berpikir kreatif matematis siswa kelas VIII di Kabupaten Bandung Barat - Mutiara, Alika; Zanthy, Luvy Sylviana; Fitrianna, Aflich Yusnita (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Being able to think creatively is crucial for kids since creativity is required to address difficulties. The purpose of this research was to find out the characteristics of creative thinking ability of high school students in relation to a  two-variable linear equation system. This study was conducted in a  high school in West Bandung district, and one class, namely class VIII B, with 23 students participated in the study. The method  used in this study is a descriptive qualitative method. This study used test instruments and non-test instruments in the form of questions and interviews. The effects confirmed that students have been able to resolve questions based on only  two indicators of creative thinking ability, ie. fluency 55.32% and flexibility 68%, and students could not  solve tasks based on news indicators one 14,44%. Based on the results of the interviews, this resulted in students who generally could not work  and solve questions with their own answers or thoughts, but only procedurally followed the SPLDV problem solving method.